Dysbiosis and Predicted Functions of the Dental Biofilm of Dairy Goats with Periodontitis - Borsanelli, Ana Carolina; Athayde, Flávia R. F. [UNESP]; Saraiva, Júlia R. [UNESP]; Riggio, Marcello P.; Dutra, Iveraldo S. [UNESP] (My University, 2022)
Periodontitis is a polymicrobial biofilm-induced inflammatory disease associated with a dysbiotic microbial community and severely affects the health and welfare of animals. However, little is known regarding the dental microbiota associated with this disease in goats. In this study, we used high-throughput sequencing, network analysis, and predicted functions to investigate the microbiota of clinically healthy goats and those with periodontitis and identify possible pathogens and proteins associated with the disease. Dental microbiomes of goats with periodontitis were richer, and network analyses showed that the number of negative interactions was higher in the networks of animals with periodontitis. Based on the interrelationships, Porphyromonas, Fusobacterium, and Prevotella were suggested to play an important role in the dental microbiota associated with goat periodontitis. Protein families linked to translation, cytoplasmatic translation, and rRNA processing were more abundant in the dental microbiota of goats with periodontitis. In conclusion, the dental biofilm microbiota associated with goat periodontitis seems to be dysbiotic and has significant antagonistic interactions, which discriminate healthy animals from diseased animals and highlight the importance of key bacteria. Thus, these novel findings contribute to the evolution of knowledge regarding the etiopathogenesis of goat periodontitis and possibly to the development of periodontitis control measures.
Keywords: Biofilm; Co-occurrence network analysis; Goat; High-throughput sequencing; Microbiota; Periodontitis